EFEK SEDIAAN HERBAL KALKUGAMA TERHADAP KALSIUM URIN DAN HISTOPATOLOGI GINJAL TIKUS UROLITIASIS KARENA INDUKSI ETILEN GLIKOL - , CHRISTINE WIJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The treatment of kidney stone (renal calculi) with surgery, endoscopy, or ultrasonic waves are relatively expensive, hence usage of drugs that could prevent and dissolve kidney stone is more preferred. Herbs that have anticalculi potential include Sonhus arvensis L., Sericocalyx crispus (L.) Bremek, and Orthosiphon aristatus which used as basic ingredients of Kalkugama. This study aims to prove anticalculi activity of Kalkugama preparation. Study was carried out on male Wistar rats, calculi forming was induced by administration of 0,75% ethylene glycol and 0,75% ammonium chloride. Preventive agent (AP) and curative agent (AK) group received 176 mg/kgBW of Kalkugama suspensions, AP from day 1 to 14th while AK from day 15 to 21th. At the end of the study, 24-hour urine of each rat was collected. Urinary volume, pH, and calcium level were measured. Blood was also sampled from each rat, then creatinine and uric acid levels in serum were measured. Kidney from each rat was taken for histopathology test. The results were analyzed statistically with ANOVA and Mann Whitney. The results of this study showed that administration of Kalkugama as a preventive agent can decrease urinary calcium level significantly (P<0.05) while administration of Kalkugama as a curative agent tend to increasing urinary calcium level (Sig.>0,05). Hence, according to urinary calcium level Kalkugama can prevent and cure the renal calculi on test rats. In addition, Kalkugama could also reduce the severity of interstitial nephritis in histopathology test of sample kidneys. Keywords: Kalkugama, anticalculi, ethylene glycol